Cloud Computing-Based Electric Payment System Application Design - Gledis S. R Mamuaya, Litania M. Walangitan, Sutari N. Sumoked (International Journal of Information Technology and Education, 2021)
Cloud Computing technology is a new paradigm in the delivery of computing services. Cloud Computing has many advantages compared to conventional systems. This article discusses cloud computing architecture in general and some examples of the implementation of cloud computing services and their benefits in electricity payments. The purpose of this study is to design a cloud computing-based electricity payment system. The method used in this research is the design thinking method. The results of this study indicate that the resulting design is good enough to be applied to a cloud computing-based electricity payment system